Caracterização de óleo de peixe e potencial de produção de biodiesel - Cardoso, Luana da Costa (2017)
Biodiesel is a renewable energy source that may replace diesel in whole or in part. New feedstocks are being researched for biodiesel production. The waste from fish processing is rich in organic and inorganic compounds, this generating concerns about the environmental impacts caused by the inadequate disposal of this material in the environment. Fish oil is one of the products that can be extracted from these residues, adding value to these fish parts and can be a feedstock alternative for biodiesel production, reducing the production costs of this biofuel and contributing to sustainability. In this sense the objective of this work was the production of biodiesel, by fish oil a feedstock in transesterification reaction with ethanol via alkaline catalysis. Some physico-chemical characteristics of fish oil were analyzed, such as moisture content, saponification number, acid number, specific mass, viscosity, iodine content and composition in fatty acids. Fish oil consists mainly of polyunsaturated fatty acids with a high acid content (10.86±0.05 mg KOH/g). In this way, the oil underwent to a neutralization treatment and the acidity reduced to 0.68±0.01 mg KOH/g, thus becaming feasible for transesterification reaction via basic catalysis. The influence of the amount of catalyst (0.5, 0.7, 1, 1.3, 1.5% m/m), molar ratio oil: alcohol (7, 8.21, 10, 11.79, 13) and temperature (30; 36; 45; 54; 60 oC) on the yield of ethyl esters was evaluated using CCD design and response surface methodology. The amount of catalyst was the variable that most influenced the transesterification of fish oil. The best operating condition was obtained at 0.7% m/m catalyst, molar ratio (oil:alcohol) of 1:11.79 and temperature of 54 oC. Finally, the characterization of the ethyl esters was determined by its moisture content, acid number, specific mass, kinematic viscosity, ester content and free glycerol content. The results showed that the physico-chemical characteristics of the ethyl esters meet the standards required by the ANP - National Agency of Petroleum, Natural Gas and Biofuels, to be considered as biodiesel.